2017
DOI: 10.1016/j.chroma.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing complex mixtures of drug-like molecules: Ion mobility as an adjunct to existing liquid chromatography-(tandem) mass spectrometry methods

Abstract: Please cite this article as: Jasper Boschmans, Filip Lemière, Frank Sobott, Analyzing complex mixtures of drug-like molecules: ion mobility as an adjunct to existing liquid chromatography-(tandem) mass spectrometry methods, Journal of Chromatography A http://dx.doi.org/10. 1016/j.chroma.2017.02.015 This is a PDF Þle of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Several reports have shown that solvents affect the formation of tautomers detected by IM-MS. Chandran et al found solvent effects must be thoroughly evaluated before a validated “standard” protocol for the quantitative determination of an analyte can be developed and recommended. In addition, Morsa et al detected the mobility peaks of acetonitrile adducts of electrophilic benzylium cations using the electrospray ionization source by trapped ion mobility spectrometer (TIMS).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that solvents affect the formation of tautomers detected by IM-MS. Chandran et al found solvent effects must be thoroughly evaluated before a validated “standard” protocol for the quantitative determination of an analyte can be developed and recommended. In addition, Morsa et al detected the mobility peaks of acetonitrile adducts of electrophilic benzylium cations using the electrospray ionization source by trapped ion mobility spectrometer (TIMS).…”
Section: Introductionmentioning
confidence: 99%
“…They used a mixture of polyalanines and drug-like compounds with known DTIM CCS values to calibrate TWIM CCS values (Figure 3). Regarding the use of this technique for separation purposes in bioanalysis, some applications can be found in combination with LC as an orthogonal separation dimension [93][94][95] or as a standalone separation technique [96]. In the latter case, a rapid and sensitive method was developed for the quantification of drugs in tissue sections using matrix-assisted laser desorption ionization (MALDI) as an ionization source.…”
Section: Travelling Wave Ion Mobility Spectrometry (Twims)mentioning
confidence: 99%
“…Ion mobility–mass spectrometry (IM–MS) is being increasingly used for structural characterization of small molecules, biomolecule folds, or even synthetic polymer folds in the gas phase. The two-dimensional shape information obtained from IM–MS as reduced ion mobility ( K 0 ) or collision cross-section (CCS) does not offer atomic level structural characterizations. Therefore, theoretical chemistry calculations are usually coupled to the IM–MS experiments.…”
Section: Introductionmentioning
confidence: 99%